We wanted a revolution black radical women, 1965-85 : new perspectives - Morris, Catherine 1970-; Hockley, Rujeko 19XX-; D'Souza, Aruna 1969- (Brooklyn Museum, 2018)
Illustrated volume to accompany an exhibition at the Brooklyn Museum opening April 2017, including an introduction by the exhibition co-curators; three scholarly critical essays; remarks from a symposium held in conjunction with the exhibition on April 21, 2017, consisting of personal reminiscences of the theater group Rodeo Caldonia; exhibition installation photographs with texts of the section introductions; an exhibition checklist; and a bibliography. An epigraph of two poems by Alice Walker will appear after the half-title page
Published on the occasion of an exhibition held at Brooklyn Museum, April 21-September 17, 2017; California African American Museum, Los Angeles, October 13, 2017-January 14, 2018; Albright-Knox Art Gallery, Buffalo, February 17-May 27, 2018; and the Institute of Contemporary Art/Boston, June 26-September 30, 2018
Includes bibliographical references (pages 143-151)
Keywords: Geschichte 1965-1994; Geschichte 1965-1985; Frauenkunst; Künstlerin; Person of Color; USA; African American feminists / Exhibitions / History / 20th century; African American women authors / Exhibitions / History / 20th century; African American radicals / Exhibitions / 20th century; African American women / Exhibitions / Political activity / 20th century; Feminist literature / Exhibitions / History / 20th century / United States; Feminism and the arts / Exhibitions / History / 20th century / United States; African American feminists; African American radicals; African American women authors; African American women / Political activity; Feminism and the arts; Feminist literature / United States; Ausstellungskatalog -- Brooklyn Museum -- 21.04.2017-17.09.2017 -- Brooklyn, NY; Ausstellungskatalog -- California Afro-American Museum -- 13.10.2017-14.01.2018 -- Los Angeles, Calif.; Ausstellungskatalog -- Albright-Knox Art Gallery -- 17.02.2018-27.05.2018 -- Buffalo, Tex.; Ausstellungskatalog -- Institute of Contemporary Art -- 26.06.2018-30.09.2018 -- Boston, Mass.